Improvement of Tuning Fork Gyroscope Drive-mode Oscillation Matched using a Differential Driving Suspension Frame - Thang Nguyen Van; Tran-Duc Tan; Hung Vu Ngoc; Trinh Chu Duc (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper presents a novel design of a vibration tuning fork gyroscope (TFG) based on a differential driving suspension coupling spring between two gyroscopes. The proposed TFG is equivalent to a transistor differential amplifier circuit. The mechanical vibrations of driving frames are, therefore, well matched. The matching level depends on stiffness of spring. When three various TFG structures respond to differential stiffness of spring, their the driving frame mechanical vibration is well matched in case the input excitation driving differential phase is less than 3.5°, 2.5°, and 4°, respectively. The fabricated tuning fork gyroscope linearly operates in the range from -200 to +200 degree/s with the resolution of about 0.45 mV/degree/s.